Yield survey and nutritional evaluation of garlic stalk for ruminant feed - Lee, Y. H. (J Anim Sci Technol, 2017)
BACKGROUND: Very limited information exists on the ruminal degradation kinetics of nutrients in garlic stalk. The present study aimed to survey the annual yield of garlic stalk in Korea and determine its feed-nutritive value for ruminants. METHODS: In Experiment 1, garlic stalk was incubated in situ in the rumen of two Hanwoo steers (360 ± 15 kg body weight) and removed after 12, 24, or 48 h to determine the ruminal degradation kinetics of DM and NDF. Rice straw was also included for comparison. In Experiment 2, In Experiment 2, six male Corriedale sheep were randomized to two dietary treatments to determine the apparent digestibility of nutrients in garlic stalk. Diets included a control ration without garlic stalk (60% concentrate mix +40% ryegrass) or a treatment ration (70% control diet +30% garlic stalk). RESULTS: The Korean national yield of garlic stalk (sun-dried basis) in 2016 was estimated to be 31,910 tons, with the southern coastal regions producing the highest quantity. Compared with rice straw, garlic stalk had lower NDF, higher ADF, and greater effective degradabilities of DM and NDF, resulting in a greater TDN value (56.3%), which was higher than that obtained for rice straw (43.7%). CONCLUSION: These results provide basic information on the ruminal DM and NDF degradation kinetics of garlic stalk, which would be helpful for the efficient utilization of this by-product in ruminant diets.